PENGARUH KEAKTIFAN BERORGANISASI DAN PRESTASI BELAJAR TERHADAP KESIAPAN KERJA MAHASISWA PROGRAM STUDI PENDIDIKAN ADMINISTRASI PERKANTORAN ANGKATAN 2013 UNIVERSITAS SEBELAS MARET SURAKARTA - Desy Fitriana Setyaningrum; Hery Sawiji; Patni Ninghardjanti (Program Studi Pendidikan Administrasi perkantoran FKIP UNS, 2018)
The objective of research was to find out: (1) the impact of organizational activity on the work readiness of Students in Office Administration Education Study Program year 2013 of Sebelas Maret University; (2) ) the impact of learning achievement on the work readiness of Students in Office Administration Education Study Program year 2013 of Sebelas Maret University; and (3) ) the impact of both organizational activity and learning achievement on the work readiness of Students in Office Administration Education Study Program year 2013 of Sebelas Maret University. This reseacrh employed a quantitative research and the sampling system used census sampling, the population of which was all student of Office Administration Education Study Program year 2013 of Sebelas Maret University, consisting 50 student. Techniques of collecting data used were questionnaire and documentation. The data was analyzed using a multiple linear regression analysis techniques with analysis prerequisite test includind normality, linearity, amd multicolinearity tests. The results of research were as follows: (1) there was a significant impact of organizational activity on the work readiness of Students in Office Administration Education Study Program year 2013 of Sebelas Maret University;(2) there was a significant impact of learning achievement on the work readiness of Students in Office Administration Education Study Program year 2013 of Sebelas Maret University;and (3) there was a significant impact of both organizational activity and learning achievement on the work readiness of Students in Office Administration Education Study Program year 2013 of Sebelas Maret University.